An optimum robot path planning with payload constraints - Saramago, Sezimaria F. P.; Ceccarelli, Marco (Robotica, 2002)
This paper presents a general methodology for the off-line planning of optimal trajectory of robot manipulators by taking into account the grasping forces in the manipulator gripper. The mechanical energy of the actuators has been considered for the formulation of the objective function. The optimization problem has been formulated as subject to physical constraints, input torque/force constraints and payload constraints. The mathematical model takes into account the coupled nonlinear equations of manipulator motion. A numerical example shows the efficiency of the proposed procedure.